2018
DOI: 10.1186/s12884-018-1845-7
|View full text |Cite
|
Sign up to set email alerts
|

Population-based trends and risk factors of early- and late-onset preeclampsia in Taiwan 2001–2014

Abstract: BackgroundPreeclampsia, a multisystem disorder in pregnancies complicates with maternal and fetal morbidity. Early- and late-onset preeclampsia, defined as preeclampsia developed before and after 34 weeks of gestation, respectively. The early-onset disease was less prevalent but associated with poorer outcomes. Moreover, the risk factors between early -and late- onset preeclampsia could be differed owing to the varied pathophysiology. In the study, we evaluated the incidences, trends, and risk factors of early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 45 publications
3
26
0
1
Order By: Relevance
“…Obstetric risk factors such as prior experience of pre-eclampsia, eclampsia and chronic hypertension may elevate a woman's risk for EO-PE. Similar to other studies [23][24][25], Our findings show that while more women who experience LO-PE had gestational diabetes and a family history of hypertension, women with EO-PE had higher rates of chronic hypertension. Severe pre-eclampsia, high sBP (>180), and high creatinine levels were all associated with EO-PE as reported elsewhere [26,27].…”
Section: Plos Onesupporting
confidence: 90%
“…Obstetric risk factors such as prior experience of pre-eclampsia, eclampsia and chronic hypertension may elevate a woman's risk for EO-PE. Similar to other studies [23][24][25], Our findings show that while more women who experience LO-PE had gestational diabetes and a family history of hypertension, women with EO-PE had higher rates of chronic hypertension. Severe pre-eclampsia, high sBP (>180), and high creatinine levels were all associated with EO-PE as reported elsewhere [26,27].…”
Section: Plos Onesupporting
confidence: 90%
“…Severe pre-eclampsia, high sBP (>180), and high creatinine levels were all associated with EO-PE. Almost half of EO-PE women had sBP over 180mmHg, while just over one third of LO-PE women had similar blood pressure rates, and the majority in both groups experienced severe pre-eclampsia-but more often among EO-PE women, similar to other studies [34][35][36][37] . There was no significant difference between the two cohorts of women (EO-PE versus LO-PE) for severity of pre-eclampsia in our study.…”
Section: Pre-eclampsia Risk Factorssupporting
confidence: 86%
“…Previous reports on population-based and case-control studies demonstrated hyperthyroidism to be associated with a high risk of preeclampsia [5][6][7][8] and placental abruption [9]. The impact of interventions for hyperthyroidism before and during pregnancy on pregnancy outcomes remains uncertain [10].…”
Section: Discussionmentioning
confidence: 99%